Socioeconomic circumstances and respiratory function from childhood to early adulthood: a systematic review and meta-analysis - Rocha, V (2019)
Objective Disadvantaged socioeconomic circumstances in early life have the potential to impact lung function. Thus, this study aimed to summarise evidence on the association between socioeconomic circumstances and respiratory function from childhood to young adulthood. Design Systematic review and meta-analysis. Methods Following the Preferred Reporting Items for Systematic Review and Meta-analysis guidelines, Medline, ISI-Web of Science and Scopus were searched from inception up to January 2018. Original studies on the association between socioeconomic circumstances and respiratory function in early ages (ie, participants younger than 25 years of age) were investigated. Two investigators independently evaluated articles, applied the exclusion criteria, extracted data and assessed the risk of bias using the Newcastle–Ottawa Scale. A meta-analysis of the standardised mean difference and 95% CI in respiratory function between participants from different socioeconomic circumstances was conducted, using a random-effects model. Results Thirty-three papers were included in this review and 23 showed that disadvantaged socioeconomic circumstances were significantly associated with reduced respiratory function. The meta-analysis including seven papers showed a significant difference of −0.31 (95% CI −0.42 to −0.21) litres in forced expiratory volume in the first second between children, adolescents and young adults from disadvantaged versus advantaged socioeconomic circumstances. Specifically a difference of −0.31 (95% CI −0.51 to −0.10) litres in girls and −0.43 (95% CI −0.51 to −0.35) litres in boys was observed. Conclusions Children, adolescents and young adults from disadvantaged socioeconomic circumstances had lower respiratory function, and boys presented higher respiratory health inequalities. This information contributes to explain the social patterning of respiratory diseases, and might enable health policy makers to tackle respiratory health inequalities at early ages.